Environmental Variables and Fisheries Diversity of the Nuwa River, Panchthar, Nepal - Limbu, Jash Hang; Prasad, Archana (Scientific World, 2020)
The fish samples were collected from October 2017 to June 2018 in Nuwa River from four sampling stations by using cast net, bamboo fish trap and mosquito nets. Environmental parameters: water temperature, dissolved Oxygen (DO), CO2, pH, hardness and water velocity were analyzed during each field visit. Eight fish species were collected in present study. The most copious species were Schizothorax plagiostomus, and Schistura multifaciatus. Shannon-Weiner fish diversity index and species richness recorded were highest at station I and lowest at station III, similarly, evenness index was highest at station I and lowest at station III. The water volume, water depth, and the availability of substrates were found to be major influential factors for the weight and length of the fishes. The redundancy analysis (RDA) portrayed that environmental variables like dissolved oxygen, free- carbon dioxide, and pH were found to be pivotal variables to shape the fish assemblage structure of Nuwa River. The cluster analysis delineated that similarity between fish species subsided as the distance of sites turgid.